Do general innovation policy tools fit all? Analysis of the regional impact of the Norwegian Skattefunn scheme - Arne Isaksen; Roger Henning Normann; Olav R. Spilling (Journal of Innovation and Entrepreneurship, 2017)
Background: The paper examines the regional effects of a general innovation policy, i.e. a policy tool that does not target specific industries or subnational regions. General policy tools are an important part of the portfolio of innovation policy measures. However, there is a question over whether general tools are equally relevant for all types of firms, irrespective of their size, sector and location. Findings: The economic geography and innovation study literature, as well as the EU's Smart Specialization approach, are based on the view that innovation policy tools must be adapted to specific regional conditions. General policy tools are insufficient unless they are adapted to individual regions. This paper examines the regional distribution of support from the Norwegian Skattefunn scheme, which is a tax incentive scheme designed to stimulate R&D activity in all types of enterprises, which has supported more than 24,000 approved R&D projects between 2002 and 2013. Based on our regression analysis, we observe that regional innovation system (RIS) variables are important for explaining the region's ability to attract Skattefunn funding. Conclusions: Skattefunn projects are quite evenly spread across labour market regions, which are grouped into a geographical centre-periphery pattern. That is, being in a peripheral location is not a disadvantage. However, at a more detailed regional level, the Skattefunn scheme tends to favour firms in specific industries and in regions with a relatively developed regional innovation system.
Keywords: 650; R&D projects; Innovation policy; Regional development; Industrial development; Skattefunn